Justice-Based Old Age Guarantee Payment Arrangements in Indonesia - Kadek Dedy Suryana; R.A Retno Murni; I Ketut Sudantra; Desak Putu Dewi Kasih (International Journal Labs, 2023)
One of the objectives of establishing the Unitary State of the Republic of Indonesia as stated in the Preamble to the 1945 Constitution of the Republic of Indonesia is to strive to improve the welfare of the people. The welfare in question must be enjoyed in a sustainable, fair, and equitable manner reaching all people. Where this is the right for every citizen to obtain social security that allows the full development of himself as a dignified human being, guaranteed by the 1945 Constitution of the Republic of Indonesia as stipulated in Article 28H paragraph (3) and Article 34 paragraph (2). Social security is also guaranteed in the United Nations Declaration on Human Rights of 1948 and affirmed in the International Labour Organization Convention No. 102 of 1952 which advocates all countries to provide minimum protection to every workforce. The national social security system is basically a state program that aims to provide certainty of protection and social welfare for all Indonesians. Through this program, every resident is expected to be able to meet the basic needs of a decent life in the event of things that can result in loss or decrease in income, due to illness, accidents, loss of work, entering old age, or retirement. The government has several programs in implementing social security, one of which is the Old Age Security Program. Old age insurance is a benefit in the form of cash that is paid in a lump sum after the participant retires, passes away, or experiences permanent total disability. The old-age Guarantee program is designed to provide protection when a person enters old age or retirement, when they no longer have income. Therefore, the name is old age guarantee.